People at the Centre Development, Resource and Displacement - Singh, Ravi S. (National Geographical Journal of India, 2022)
The development discourse has been continuosly envolving, especially since the mid-20th century. The known literature clearly indicates how people have been struggling since historical times for their existence, survival, and well-being and welfare. The man-nature relationship in one hand, and the nature and intensity of struggles on the other have undoubtedly undergone remarkable change. The present article looks at the relationship between development-resource-environment and the current development practices which impact both people and environment adversely, conflicts included, from a critical perspective. It also addresses the bigger problem of displacement of people from their places, mostly involuntary, triggered together by development projects and disasters, and the state's response to it. The analysis attempted leads to the conclusion that displaced persons are not given sufficient and proper attention as revealed by the higher percentage of backlogs in rehabilitation and resettlement and meagre compensation. Every displacement, whether as fallout of development process or deteriorating environment caused disasters, requires appropriate and timely state intervention by the state as well as civil society for effective redressal of the problems faced by the affected people.